Utilization of Electroplating Sludge as Subgrade Backfill Materials: Mechanical and Environmental Risk Evaluation - Yu Zhang; Peixin Shi; Lijuan Chen; Qiang Tang (Advances in Civil Engineering)
The electroplating sludge may pose serious threat to human health and surrounding environment without safe treatment. This paper investigated the feasibility of using electroplating sludge as subgrade backfill materials, by evaluating the mechanical properties and environmental risk of the cement-coal fly ash solidified sludge. In this study, Portland cement and coal fly ash are used to solidify/stabilize the sludge. After curing for 7, 14, and 28 days, the stabilization/solidification sludge specimens were subject to a series of mechanical, leaching, and microcosmic tests. It was found that the compressive strength increased with the increase of cement content, curing time, and the cement replacement by coal fly ash besides water content. Among these factors, the impact of water content on the compressive strength is most noticeable. It was observed that the compressive strength declined by 87.1% when the water content increased from 0% to 10%. Besides, leaching tests showed that the amount of leaching heavy metals were under the standard limit. These results demonstrated utilization of electroplating sludge in subgrade backfill material may provide an alternative for the treatment of electroplating sludge.